2021
DOI: 10.30595/psychoidea.v19i1.7737
|View full text |Cite
|
Sign up to set email alerts
|

Menjadi Pensiunan Optimis Dan Tangguh: Korelasi Optimisme Dan Resiliensi Pada Pensiunan Tni-Al

Abstract: Saat memasuki masa pensiun, Tentara Nasional Indonesia akan menghadapi berbagai perubahan, misalnya dalam hal keuangan, status, aktivitas, dan lain-lain. Perubahan tersebut membutuhkan kemampuan untuk penyesuaian. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara optimisme dengan resiliensi pada pensiunan TNI-AL. Subjek pada penelitian ini adalah pensiunan TNI-AL (30 partisipan). Teknik pengambilan sampel dalam penelitian ini adalah dengan tipe non probability sampling: purposive sampling. Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…From the results of previous studies, it was found that optimism plays an important role in increasing resilience in first-year students (Dawson & Pooley, 2013). Likewise with previous research which suggested that optimism has a contribution to increasing resilience in retired TNI-AL (Putri & Alfinuha, 2021).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…From the results of previous studies, it was found that optimism plays an important role in increasing resilience in first-year students (Dawson & Pooley, 2013). Likewise with previous research which suggested that optimism has a contribution to increasing resilience in retired TNI-AL (Putri & Alfinuha, 2021).…”
Section: Introductionsupporting
confidence: 53%
“…Optimism has an important contribution in the process of building resilience. Resilience will be difficult to form without the role of optimism (Missasi & Izzati, 2019;Putri & Alfinuha, 2021;Roellyana & Listiyandini, 2016). In this case, especially for employees who have experienced layoffs, previous research argues that individuals who have good resilience are due to the role of optimism, where individuals believe that everything can change for the better (Khodabakhshi-Koolaee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pada penelitian sebelumnya, semakin tinggi optimisme seorang pensiunan, maka semakin tinggi pula resiliensi individu tersebut, dan begitu pula sebaliknya. Ketika individu memiliki suatu tujuan dan yakin bahwa hal yang akan terjadi di masa depan adalah hal yang baik, akan membuat individu tersebut memiliki kapasitas kemampuan beradaptasi (resiliensi) yang baik [19].…”
Section: "Enggak Sih Mba Malah Enak Ya Mba Soalnya Udah Bebas Gak Har...unclassified